Necessary Leaven: Hypocrisy and the Heptaméron - Butterworth, Emily (Renaissance and Reformation / Renaissance et Réforme, 2020)
Hypocrisy is a recurring concern in Marguerite de Navarre’s Heptaméron, part of the wider dynamic of dissimulation, pretence, and exposure explored in the storytelling project. This article discusses the contexts in which hypocrisy is revealed and debated in the Heptaméron. While clerical and feminine hypocrisies are familiar from medieval discussions of lecherous friars and unchaste women, Marguerite de Navarre’s evangelical emphasis presents hypocrisy more generically as an inevitable consequence of the Fall. Beyond general statements about the human condition, there emerges a more nuanced condemnation of hypocrisy that acknowledges relative positions of power and exploitation.